THE RELATIONSHIP BETWEEN BODY CONDITION SCORE (BCS) AND TESTICULAR SIZE IN BALINESE CATTLE - Rivan Stefanus Fina; Reni Ratni Dapawole; Edelnia Kristian Bere (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
This study aimed to determine the relationship between Body Condition Score (BCS) and testicular size (length) in male Bali cattle. The research method employed was quantitative correlational using simple linear regression and correlation analysis. The research sample consisted of 8 male Bali bulls aged 2 years old, categorized into variations of BCS groups 2, 3, and 4. Data collection was conducted through visual assessment and palpation to determine the BCS status, alongside macromorphometric measurements of testicular length using a measuring tape. The results showed an average BCS value of 3,000 ± 0,756. Based on the BCS grading scale of 2–4, a BCS value of 3 indicates that the Bali bulls were in ideal condition. Meanwhile, the average testicular length obtained was 8,813 ± 1,033 cm, reflecting normal and uniform growth of the external reproductive organs for the 2-year-old age group. Based on the simple linear regression analysis, the regression equation was formulated as Y = 6.188 + 0.875 X with a correlation coefficient (r) of 0.640, indicating a direct (positive) relationship with a moderate-to-strong level of closeness. However, the significance test showed that the relationship between the two variables was not significantly different or non-significant (P >0.05) since the calculated r-value (0.640) was smaller than the table r-value (0.707). The study concludes that 2-year-old male Bali bulls exhibit proportional body condition and normal testicular length with a positive-linear relationship, though its statistical effect is non-significant. This proves that the development of testicular size is not solely determined by temporary physical body condition but is strongly influenced by other internal and external factors such as genetics, age, body weight, and environment. Therefore, BCS assessment is suggested only as an initial indicator, while the selection of superior bulls must still be carried out comprehensively by involving other reproductive morphometric parameters.